2014
DOI: 10.3390/ijerph110202108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age, Season, Gender and Urban-Rural Status on Time-Activity: Canadian Human Activity Pattern Survey 2 (CHAPS 2)

Abstract: Estimation of population exposure is a main component of human health risk assessment for environmental contaminants. Population-level exposure assessments require time-activity pattern distributions in relation to microenvironments where people spend their time. Societal trends may have influenced time-activity patterns since previous Canadian data were collected 15 years ago. The Canadian Human Activity Pattern Survey 2 (CHAPS 2) was a national survey conducted in 2010–2011 to collect time-activity informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
184
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(196 citation statements)
references
References 16 publications
7
184
1
4
Order By: Relevance
“…Given the positive hedonic outcomes, one may question why people are not spending time in nature (Evans & McCoy, 1998;MacKerron & Mourato, 2013;Matz et al, 2014). One explanation for this disconnect is that nature's effects on wellbeing are underappreciated.…”
Section: Nature and Hedonic Wellbeingmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the positive hedonic outcomes, one may question why people are not spending time in nature (Evans & McCoy, 1998;MacKerron & Mourato, 2013;Matz et al, 2014). One explanation for this disconnect is that nature's effects on wellbeing are underappreciated.…”
Section: Nature and Hedonic Wellbeingmentioning
confidence: 99%
“…The shift to urban living is expected to continue and become even more pronounced as the twenty-first century progresses. In financially wealthy, industrialized nations, less than 10% of each day, on average, is spent outdoors (Evans & McCoy, 1998;MacKerron & Mourato, 2013;Matz et al, 2014) and per capita participation in nature-based recreation is declining (Pergams & Zaradic, 2008). Children are spending less time outdoors (Louv, 2005), opting for large amounts of screen time instead (Rideout, Foehr, & Roberts, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of time-activity patterns have shown that Canadian adults spend an average of 69% of their time in indoor residential environments with an increased amount of time spent indoors at home during winter (1 h 11 min on average) compared to summer (Matz et al, 2014;Wheeler et al, 2011). Several studies have been undertaken in Fort McKay, Alberta during the past 10 years to examine indoor/outdoor relationships of sulfur dioxide (SO 2 ) and volatile organic compounds (VOCs), and personal exposure to VOCs (Hoeksema and Kindzierski, 2010;Kindzierski and Miyagawa, 2007;Kindzierski and Ranganathan, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that most people spend almost 90% of their time indoors. 11 The amount of time spent at home is likely to be increased for young children and elderly populations and this could result in increased susceptibility to personal exposure to indoor fungal bioaerosols.…”
Section: Introductionmentioning
confidence: 99%